2019
DOI: 10.1177/2325967119889331
|View full text |Cite
|
Sign up to set email alerts
|

Performance After Operative Versus Nonoperative Management of Shoulder Instability in the National Basketball Association

Abstract: Background:Although nonoperative management after shoulder instability injury allows an athlete to return to play sooner than operative intervention, higher rates of recurrence have been observed after nonoperative management. However, no study has investigated the differences in performance of National Basketball Association (NBA) players after index shoulder instability events managed nonoperatively versus operatively.Purpose/Hypothesis:The purpose of this study was to identify shoulder instability events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Performance analysis demonstrated that those with high baseline true shooting percentages and high win shares per 48 minutes were more likely to benefit from surgical stabilization. 30 PER may decrease in those managed nonoperatively in the season after injury (15.2 ± 4.2 vs 11.9 ± 6.9; P = .017) but not by postinjury season 3 (13.5 ± 6.4; P = .20). 30 Other studies did not show differences in performance between patients and controls.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Performance analysis demonstrated that those with high baseline true shooting percentages and high win shares per 48 minutes were more likely to benefit from surgical stabilization. 30 PER may decrease in those managed nonoperatively in the season after injury (15.2 ± 4.2 vs 11.9 ± 6.9; P = .017) but not by postinjury season 3 (13.5 ± 6.4; P = .20). 30 Other studies did not show differences in performance between patients and controls.…”
Section: Resultsmentioning
confidence: 90%
“… 30 PER may decrease in those managed nonoperatively in the season after injury (15.2 ± 4.2 vs 11.9 ± 6.9; P = .017) but not by postinjury season 3 (13.5 ± 6.4; P = .20). 30 Other studies did not show differences in performance between patients and controls. 24…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations